2004
DOI: 10.1063/1.1808120
|View full text |Cite
|
Sign up to set email alerts
|

Influence of molecular adsorption on the dielectric properties of a single wall nanotube: A model sensor

Abstract: Recent measurements of the resonance frequency of a copper disk covered with carbon nanotube bundles have shown characteristic resonance shifts during exposure with various gas molecules. The shifts were interpreted as the change of the dielectric permittivity of the system forming the sensor due to the electric properties of the adsorbed molecules. Starting from a simplified sensor model formed by one single wall nanotube, we develop a self-consistent approach to describe the variation of the linear dielectri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
38
0

Year Published

2006
2006
2014
2014

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 42 publications
(42 citation statements)
references
References 30 publications
4
38
0
Order By: Relevance
“…2 represents the typical X-ray diffraction patterns obtained from the pure nanocrystalline ceria sample, and for the x = 15 wt.% composite sample. In full agreement with literature results [17][18][19]32], the two characteristic Bragg peaks of CNTs corresponding to the (0 0 2) and the (1 0 1) in the XRD pattern, are observed in this last sample close to the angle of 2 = 26.5 • . The ceria polycrystalline phase is clearly evidenced through the Bragg peaks of fluorite structure (JCPDS 89-8436): these diffraction peaks are systematically broadened, which confirms the nanostructuration of ceria phase.…”
Section: Microstructuressupporting
confidence: 78%
See 3 more Smart Citations
“…2 represents the typical X-ray diffraction patterns obtained from the pure nanocrystalline ceria sample, and for the x = 15 wt.% composite sample. In full agreement with literature results [17][18][19]32], the two characteristic Bragg peaks of CNTs corresponding to the (0 0 2) and the (1 0 1) in the XRD pattern, are observed in this last sample close to the angle of 2 = 26.5 • . The ceria polycrystalline phase is clearly evidenced through the Bragg peaks of fluorite structure (JCPDS 89-8436): these diffraction peaks are systematically broadened, which confirms the nanostructuration of ceria phase.…”
Section: Microstructuressupporting
confidence: 78%
“…7) is higher for the 15 wt.% sample. Our results can be compared with previous results obtained by gas chromatography (GC) [17][18][19][20]: the authors showed that the catalytic activity started from 50 • C (which corresponds to the beginning of the CO conversion). They observed that the complete CO conversion systematically occurred at 300 • C for all samples: in their work, the authors investigated nano-ceria, nanorods and individual nanotubes (without any DWNTs support).…”
Section: Solid-gas Interactions and Ftir Analysessupporting
confidence: 50%
See 2 more Smart Citations
“…The calculations are performed for different values of ϵ in order to simulate a static screening due to the intrinsic permittivity of the nanotube and the environmental influence. The intrinsic dielectric constant ϵ NT for nanotubes and for graphene is approximately 4ϵ 0 (with ϵ 0 being the vacuum permittivity) [29]. For this reason, in the following analysis, we focus on what happens for ϵ ¼ 4ϵ 0 .…”
mentioning
confidence: 99%